The field guide - DiTerlizzi, Tony (DiTerlizzi, Tony. Spiderwick chronicles, 2003)
When the Grace children go to stay at their Great Aunt Lucinda's worn Victorian house, they discover a field guide to fairies and other creatures and begin to have some unusual experiences.